A study into the roles of cu/tio2 photocatalysts in the of methylene blue photodecomposition and water photo-splitting - Chong, Soo Kee (2014)
Several papers have addressed the production of H2 from water using catalyst. One of the most innovative ways is via photocatalysis. In this study, titania act as the base catalyst on which copper dopant varies the physicochemical properties. Ultimately, this work was aimed to synthesized and investigated the physicochemical properties of titania supported copper, (Cu/TiO2) photocatalyst for photoreaction of glycerol solution. The photocatalyst, Cu/TiO2 was prepared via wet impregnation method with doped 2, 5, 10, 15, 20 and 25 wt% of Cu. X-ray fluorescence (XRF) showed that the composition of Cu followed the doped weight percentage on TiO2 and liquid-nitrogen physisorption showed that the BET specific surface area decreased with the increment of Cu loading. Thermogravimetric analysis (TGA) showed that Cu decomposed around 450 to 550 K while X-ray diffraction (XRD) proved the Cu/TiO2 was anatase with a new peak 2θ = 13° found as the appearance peak of CuO species. The measured densities were differed from the theoretical calculated densities. The photoreactivity of Cu/TiO2 was tested with methylene blue decomposition and the results have indicated that Cu/TiO2 possessed photoreactivity. The conversions for all the photocatalysts with Cu loading were higher than the pristine TiO2. This has confirmed that Cu loading has effectively increased the photoreaction of methylene blue solution. The 15 wt% Cu/TiO2 photocatalyst showed the highest conversion at 44%. For loadings lower than 15wt%Cu, the photocatalytic activity increased with Cu deposition on TiO2. The concentration profiles were fitted to the first order reaction rate law, the rate constant for each Cu/TiO2 was calculated and 15 wt% Cu/TiO2 has the highest rate constant (9.70 10-3 min-1). The photocatalyst loading and concentration loading were conducted. In photocatalyst loading study, 1.0 g/L of 15 wt% Cu/TiO2 can be concluded as the optimum weight loading for 300 mL of MB solution. In the concentration study, the amount of photocatalyst (0.25g) considered not optimum to yield the maximum conversion. The photocatalytic performance of Cu/TiO2 photocatalyst in various copper loadings has revealed that hydrogen generation activity was disadvantageous of high copper loading as it displayed an inferior activity